First Occurrence of Plagioporus skrjabini Kowal, 1951 (Trematoda: Opecoelidae) in Iraq from the Sisorid Catfish Mystus pelusius - N. Abdul-Ameer, Kefah; J. Kadhim, Yasamin; J.Taher, Ahlam (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The trematode Plagioporus skrjabin iKowal, 1951 was recorded in this study for the first time in Iraq from intestine of Mystus pelusius (Solander, 1794) which were collected from different locations along Tigris River near Al-Shawwaka region, Baghdad city. The description and measurements of this parasite as well as its illustration were given.